DOENÇAS SEM DOENTES: OCORRÊNCIA DE DISTÚRBIOS OSTEOMUSCULARES RELACIONADOS AO TRABALHO – DORT NOS OPERADORES DE CAIXA DE UM BANCO - Moizés Martins Junior; Maria Christine Werba Saldanha (Ação Ergonômica)
The changes incurred in the financial system with the introduction of new technologies and new forms of administration of banks has caused impact on the health of workers. The Work-Related Musculoskeletal Disordes - WRMD represent a group of occupational diseases always present among these workers, notably in the bank tellers. This paper aims to search the occurrence of WRMD in the activity. Methodological tools of ergonomics are used to provide a broad knowledge of aspects of work that have been studied and influential in the generation of occupational diseases studied. They have also noted cases of illness for DORT workers without fulfilling the legal requirement of the issuance of the communication of labour accident and without the removal of the employee of the workplace. The reasons that lead the company to evade information about the occurrence of WRMD are not admitting the existence in the workplace of the causal agent of diseases of the employee, ensure that the employee get the benefit of stability accident, do not deposit the contribution of 8% of FGTS, not to admit his guilt as a generator of occupational disease t and not to increase pension statistics.